2020
DOI: 10.3390/su12208491
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Electrochemical Enhancement of Hydrogen and Methane Production in a Combined Anaerobic Digester (AD) and Microbial Electrolysis Cell (MEC) from Dairy Manure

Abstract: Anaerobic digestion (AD) is a biological-based technology that generates methane-enriched biogas. A microbial electrolysis cell (MEC) uses electricity to initiate bacterial oxidization of organic matter to produce hydrogen. This study determined the effect of energy production and waste treatment when using dairy manure in a combined AD and MEC (AD-MEC) system compared to AD without MEC (AD-only). In the AD-MEC system, a single chamber MEC (150 mL) was placed inside a 10 L digester on day 20 of the digestion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 46 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…The maximum methane production rate from this work (30.35 mL/L ≈ 0.031 m 3 /m 3 /day) using unassimilated bioanode (rate limited separation technique) was equal to 11.54% of the CH 4 production rate obtained by the previously reported anaerobic digestion (AD) coupled MEC system (0.26 m 3 /m 3 /day). 33 This comparative analysis indicated that the obtainable CH 4 solely from unassimilated MEC fed with dairy manure wastewater was of moderate quantity and more research work in this area could shift the focus toward the unassimilated MEC system.…”
Section: Bioenergy Production From the Unassimilated Anodementioning
confidence: 93%
See 1 more Smart Citation
“…The maximum methane production rate from this work (30.35 mL/L ≈ 0.031 m 3 /m 3 /day) using unassimilated bioanode (rate limited separation technique) was equal to 11.54% of the CH 4 production rate obtained by the previously reported anaerobic digestion (AD) coupled MEC system (0.26 m 3 /m 3 /day). 33 This comparative analysis indicated that the obtainable CH 4 solely from unassimilated MEC fed with dairy manure wastewater was of moderate quantity and more research work in this area could shift the focus toward the unassimilated MEC system.…”
Section: Bioenergy Production From the Unassimilated Anodementioning
confidence: 93%
“…as well as from wastewater substrates having microbial community present in them. 25,27,[31][32][33] The breakdown of the organic content present in substrates having no microbial community is difficult and therefore prior assimilation is needed, to produce electrons and protons. 20,34 Organic wastewater has already grown microbial community in them, and they can break their organic contents without prior assimilation.…”
mentioning
confidence: 99%
“…Microbial electrolysis cells (MEC) are a type of bioelectrochemical system capable of degrading organic matter and, depending on the cell configuration, producing hydrogen (H 2 ) and/or methane (CH 4 ) with the aid of a small energy input [8,9]. Previous research by several authors has shown that the integration of a MEC-AD system can improve the overall performance of the system by showing (i) an increase in methane production yields; (ii) improved process stabilization; (iii) high organic matter removal; and (iv) conversion of hydrogen ions and volatile fatty acids into methane [10][11][12][13][14][15][16][17][18][19]. For instance, Moreno et al [10] reported an improvement in the degradation of the organic matter contained in domestic wastewater by a MEC and an increase in the methane production rate versus a conventional AD.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Moreno et al [10] reported an improvement in the degradation of the organic matter contained in domestic wastewater by a MEC and an increase in the methane production rate versus a conventional AD. Hassanein et al [12] improved productivity from 10.9 L CH 4 by AD to 23.6 L CH 4 via MEC in addition to increasing the chemical oxygen demand (COD) removal by applying a cell potential of 1 V. Finally, Zhao et al [14] observed an increase in methane production from 23.8 to 45.6% in the MEC-AD reactor compared to the traditional one using acetate as a substrate. It has also been observed that the influence of using different types of wastes/compounds as substrates in MEC-AD systems could lead to a higher methane production yield compared against traditional AD [11,16,17,19].…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude that high MEC manufacturing cost, high internal resistance, methanogenesis, and membrane/cathode biofouling are the main limiting factors in the scale-up of this technology. To increase hydrogen production Hassanein et al, combined MEC technology with anaerobic digestion [16]. A comparative study between MEC and AD-MEC was conducted, and it was concluded that cumulative H 2 and CH 4 production and COD removal were higher in AD-MEC as compared to AD-only.…”
mentioning
confidence: 99%